1998
DOI: 10.1007/s007050050455
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and physicochemical characterization of the hepatitis C virus recovered from the serum of an agammaglobulinemic patient

Abstract: Hepatitis C virus (HCV) morphology and physicochemical properties remain unclear because HCV usually circulates in a complexed form in association with immunoglobulins. In the present work, we were interested in the characterization of HCV particles derived from the serum of an anti-HCV negative/HCV RNA positive agammaglobulinemic patient suffering from chronic type C hepatitis. Physicochemical properties of the virus particles were determined by serum centrifugation on a 10-60% isopycnic sucrose density gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
14
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
5
14
0
Order By: Relevance
“…Some previous observations have suggested that HCV core antigen-expressing viral structures may be present in the sera of HCV-infected individuals: a proportion of a high-density HCV population detected by RT-PCR was precipitated by anti-core antibodies (7,13,18), HCV core antigen has been detected in some serum samples by ELISA (25), and a few 45-nm-diameter nucleocapsid-like particles have been observed in the serum of an agammaglobulinemic patient by electron microscopy (42). Our data clearly show that the HCV nucleocapsid, which is thought to be present in the blood- stream as an internal component of infectious virions, is present in the sera of patients also as a free, nonenveloped particle and is synthesized in large amounts in the baculovirus expression system in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…Some previous observations have suggested that HCV core antigen-expressing viral structures may be present in the sera of HCV-infected individuals: a proportion of a high-density HCV population detected by RT-PCR was precipitated by anti-core antibodies (7,13,18), HCV core antigen has been detected in some serum samples by ELISA (25), and a few 45-nm-diameter nucleocapsid-like particles have been observed in the serum of an agammaglobulinemic patient by electron microscopy (42). Our data clearly show that the HCV nucleocapsid, which is thought to be present in the blood- stream as an internal component of infectious virions, is present in the sera of patients also as a free, nonenveloped particle and is synthesized in large amounts in the baculovirus expression system in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…While the sedimentation coefficient calculated for HCV both in vivo and in vitro falls into the range described for other Flaviviridae (ϳ200S) (32), the broad density range of the particles in the supernatant appears to be a unique feature characteristic of HCV (1,22,25,30,36,40,43,48,49,51,54). This broad range of buoyant densities is thought to be partially dependent on the presence of host lipoprotein components, including apoB and apoE, in the viral particle (1,40,47,48).…”
mentioning
confidence: 84%
“…Previous ultrastructural studies using patient-derived material report particles with heterogeneous diameters ranging from 35 to 100 nm (33,37,42,57,64). Cell culture-derived particles appear to display a diameter within that range (ϳ55 nm) (65,68).…”
mentioning
confidence: 89%